Atorvastatin suppresses interferon-γ-induced neopterin formation and tryptophan degradation in human peripheral blood mononuclear cells and in monocytic cell lines - NEURAUTER, G (Blackwell Publishing Inc, 2003)
Inhibitors of 3-hydroxy-3methylglutaryl-co-enzyme A (HMG-CoA) reductase, so-called statins, are used in medical practice because of their lipid-lowering effect and to reduce the risk of coronary heart disease. Recent findings indicate that statins also have anti-inflammatory properties and can modulate the immune response. In vitro, we investigated the effect of atorvastatin on the T cell/macrophage system in peripheral blood mononuclear cells (PBMC) and in the human monocytic cell lines THP-1 and MonoMac6. We monitored neopterin production and tryptophan degradation in PBMC after treatment with 10 µm and 100 µm atorvastatin in the presence or absence of 100 U/ml IFN-γ, 10 µg/ml phytohaemagglutinin (PHA) or 10 µg/ml concanavalin A (ConA) and in monocytic cell lines THP-1 and MonoMac6 with or without stimulation with 100 U/ml IFN-γ or 10 ng/ml to 1 µg/ml lipopolysaccharide (LPS). In stimulated PBMC 100 µm atorvastatin inhibited neopterin formation and tryptophan degradation completely, whereas 10 µm atorvastatin was only partially effective. Also in monocytic cell lines THP-1 and MonoMac6, atorvastatin was able to suppress IFN-γ- and LPS-induced formation of neopterin and degradation of tryptophan. Our data from PBMC agree well with previous investigations that statins inhibit T cell activation within the cellular immune response. In addition we demonstrate that atorvastatin directly inhibits IFN-γ-mediated pathways in monocytic cells, suggesting that both immunoreactivity of T cells and of monocyte-derived macrophages are down-regulated by this statin.